Early Russian evangelicals (1874-1929) : historical background&hermeneutical tendencies based on I.V. Kargel’s written heritage - Hofmeyr, J.W. (Johannes Wynand), 1947- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.